LEXICAL SEMANTIC CHARACTERISTICS OF HYPONYMY IN ENGLISH- UZBEK LANGUAGES (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the lexical semantic characteristics of hyponymy in the context of the English and Uzbek languages. Hyponymy, a fundamental aspect of lexical semantics, plays a crucial role in understanding the hierarchical structure of word meanings within a language. By employing a comparative analysis, this study aims to highlight similarities and differences in hyponymic relations between English and Uzbek, shedding light on the intricacies of semantic structures in these languages.